2011
DOI: 10.1590/s0004-27302011000700007
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical hypothyroidism and risk to carotid atherosclerosis

Abstract: Objective: The aim of this study was to assess whether subclinical hypothyroidism (SCH) is associated with carotid atherosclerosis, as well as dyslipidemia, and arterial hypertension. Subjects and methods: The study included 69 consecutive patients with newly diagnosed SCH, and 30 matched healthy controls. Body mass index (BMI), TSH, fT4, antibodies to thyroid peroxidase (TPOabs), lipids, blood pressure, mean and maximum carotid intima-media thickness (CIMT) were determined in all participants. Results: Mean v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 26 publications
4
33
1
4
Order By: Relevance
“…Overt and subclinical hypothyroidism are well-established risk factors for atherosclerosis. 1,2 Patients with subclinical hypothyroidism are more likely to have an increased CIMT and a higher prevalence of carotid plaques, 1,17 and levothyroxine replacement therapy in these patients reduced CIMT and improved cardiovascular risk factor levels and endothelial function. 18,19 Studies of the association between thyroid hormone levels in the euthyroid range and atherosclerosis, however, have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Overt and subclinical hypothyroidism are well-established risk factors for atherosclerosis. 1,2 Patients with subclinical hypothyroidism are more likely to have an increased CIMT and a higher prevalence of carotid plaques, 1,17 and levothyroxine replacement therapy in these patients reduced CIMT and improved cardiovascular risk factor levels and endothelial function. 18,19 Studies of the association between thyroid hormone levels in the euthyroid range and atherosclerosis, however, have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional theory held that insufficient thyroid hormone (TH) caused AS (Ichiki 2010). However, subclinical hypothyroidism (SCH) has also been related with AS (Valentina et al 2011). TH is maintained at normal levels in patients with SCH, whereas thyroid-stimulating hormone (TSH) is increased.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies investigating the systolic and diastolic function of the heart in ScH showed controversial results. Some studies demonstrate mild diastolic dysfunction in patients with ScH [4][5][6][7][8][9], but not in others [10][11][12][13]. Diastolic dysfunction increases morbidity, leading to no effort tolerance and occurrence of heart failure.…”
Section: Introductionmentioning
confidence: 99%